The Effect of Process Parameters on Microstructure and Porosity of Layered NiAl(Co/Cr) Alloy Produced by SHS Method - Biliz, Ibrahim; Bakkaloglu, Adem; Kilic, Musa (GAZI UNIV, 2020)
This paper deals with the investigation of microstructure and porosity of layered compounds of NiAl(Co/Cr) powders by SHS method. Layers of 50% Ni-50% Al powders were mixed with 3%, 6% and 10% of Co and Cr powders. These were mixed for 12 hours in a rotational container with a speed of 300 rpm. Mixed powders were cold compressed in a mould with pressures of 50, 100 and 200 MPa. The obtained samples were then synthesized in an argon controlled atmosphere with and without preheating to 250 degrees C. The microstructure of synthesized samples was analysed using SEM-BSE, EDS and XRD. The EDS results showed that the samples were containing Ni in majority along with Al, Co, and Cr. To determine the phase components, XRD spectra was analysed and the peaks of NiAl, Ni3Al, and NiAl3 were confirmed with NiAl having the highest peak intensity. The density calculations showed that the ratio of pores was affected the most from pressure. The main reason for this was attributed to the better contact of the powders under higher pressure which helped an uninterrupted reaction. The highest pore ratio values were obtained from samples produced under 50 MPa pressure.
Keywords: NiAl; NiAlCoCr; nickel aluminide; SHS; porosity; Engineering